Factors associated with upper limb function in breast cancer survivors. Issue 2 (23rd November 2021) - Roldán‐Jiménez, Cristina; Martín‐Martín, Jaime; Pajares, Bella; Ribelles, Nuria; Alba, Emilio; Cuesta‐Vargas, Antonio I.
Abstract: Background: Breast cancer survivors may have side effects from treatment, such as impaired upper limb function after surgery, which may be affected by a range of factors. Objective: To analyze the association between upper limb function and strength, fear avoidance, and central sensitization symptoms among breast cancer survivors, and to explore how these variables are associated with upper limb function. Design: Validation cohort. Setting: Institutional practice at a public hospital. Patients: One hundred seventy‐four breast cancer survivors who had been undergone surgery for a primary tumor. Interventions: Not applicable. Main Outcome Measure: Upper limb function was measured by the Upper Limb Functional Index (ULFI‐Sp). Independent outcomes were: handgrip strength, which was measured using a Jamar dynamometer on the dominant side; fear avoidance, measured using the Fear‐Avoidance Components Scale (FACS‐Sp); and central sensitization symptoms, which were measured using the Central Sensitisation Inventory (CSI‐Sp). A linear regression model explaining the ULFI‐Sp results was constructed with the variables. Results: The regression model was significant (F = 46.826; p < .0001), and explained 45% of the variance of the ULFI values. All variables showed strong associations with upper limb function. Conclusions: Greater upper limb function is associated with higher grip strength, lower fear‐avoidance behavior and fewer central sensitization symptoms among breast cancer survivors. These variables explained 45% of the upper limb function in the regression model, and concur with earlier research showing that factors such as central sensitization symptoms and kinesiophobia negatively affect upper limb function in such patients. Clinicians should therefore take into account strength, fear avoidance, and central sensitization symptoms when considering interventions aimed at improving upper limb function among breast cancer survivors.